Pentingnya Pendidikan Toleransi bagi Para Peserta Didik dari Presfektif Pendidikan Agama Katolik - Arun Rante Limbong; Frans Fandy Palinoan; Anthonius Michael (Journal on Education, 2021)
This research aims to examine and analyze the role of tolerance education in the world of education, especially for students. The method used by the authors in this research is the library research method, which is a series of activities related to library data collection methods. According to Abdul Rahman Sholeh, library research is research that uses methods to obtain information data by placing existing facilities in libraries such as books, magazines, documents, records of historical stories or pure literature research related to the object of research. The results of this study indicate that tolerance education has a central role in the world of education, especially for students in developing their social life.